Inflammatory Caspases: Targets for Novel Therapies - Cornelis, Sigrid; Kersse, Kristof; Festjens, Nele; Lamkanfi, Mohamed; Vandenabeele, Peter (Current Pharmaceutical Design, 2007)
This review provides an overview of the biochemistry and activation of inflammatory caspases, and focuses on their therapeutic potential as disease targets in pathologies such as sepsis, Crohn´s disease, rheumatoid arthritis, traumatic brain injury and amyotrophic lateral sclerosis (ALS). We summarize the proof-of-principal evidence obtained by studies in several corresponding experimental disease models confirming the validity of strategies targeting inflammatory caspases. We discuss the use of inflammatory caspase inhibitors, such as VX-740 (Pralnacasan) and VX-765, in clinical studies for rheumatoid arthritis and osteoarthritis. Finally, we point out recent approaches identifying novel peptidomimetic or non-peptide caspase inhibitors with suitable clinical profiles.
Keywords: pralnacasan